Comparação das respostas psicofisiológicas entre o exercício intervalado de alta intensidade em esteira e com elástico em adultos saudáveis - Nunes, Lenice Brum (2023)
The objective of this study was to compare the acute psychophysiological responses (i.e., affective response, enjoyment and mood) between high-intensity interval training with elastic resistance (EL-HIIT) vs. high-intensity treadmill interval training (HIIT) in healthy adults. Eighteen healthy adults (26.6 ± 3.9 years) performed randomized HIIT and EL-HIIT sessions. Sessions were prescribed 10 × 1 min at ~85% V̇ O2max separated by 1 min interval, prescribed by specific cardiopulmonary tests. The affective response was assessed before, at the end of each effort and 10 min after. The mood profile was assessed before and after each session, and enjoyment was assessed only at the end of the sessions. A two-way ANOVA for repeated measures was applied followed by Tukey's post hoc test to compare affective response and mood between HIIT and EL-HIIT. The paired t test was used to evaluate enjoyment. Results: EL-HIIT showed a less positive affective response in efforts 5, 6, 7 and 10 during the session compared to HIIT (p<0.05). The affective response 10 min later was more positive for EL-HIIT. Only EL-HIIT reduced the feeling of depression and mental confusion compared to measures assessed before the session (p<0.05). Still, there was no difference in mood states comparing EL-HIIT and HIIT. Conclusion: An EL-HIIT session provides positive psychophysiological responses similar to HIIT after exercise. However, EL-HIIT presents a more pronounced decline in the affective response during the session compared to HIIT.